A Study on Policy Holder's Expectation and Preference towards Selected Private Life Insurance Companies in Karur District - Panchanatham, N.; Jhansi, S.; Kumar, S.Senthil; Mani, A. (Indian Journal of Marketing, 2008)
In this highly competitive environment, a company's success largely depends on the frequent launch of new products to satisfy the constantly changing consumer preferences. However, launching new products can be an attractive growing strategy but not risk free. Therefore, an increasing number of firms have turned to brand extension- a popular strategy to launch new products under existing brand names. There are many different perspectives on brand extensions but in this paper we didn't focus on all those views. This paper provides a broad summary of current thoughts on the brand extensions. Specifically, the present article provides a resource to aid in understanding brand extension, its dimensions, directions, its benefits as a marketing strategy and also the risk associated with it. Some success factors are also discussed which make brand extension successful. The last section covered some managerial implications and recommendations which might be enhance the success of brand extension in the market.